2008
DOI: 10.1021/ja808329f
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Carbon Nitride Solids by Protonation: Morphology Changes, Enhanced Ionic Conductivity, and Photoconduction Experiments

Abstract: Covalently bonded carbon nitride materials (e.g., g-C(3)N(4)) have numerous potential applications ranging from semiconductors to fuel cells. But their solubility is poor, which makes characterization and processing difficult. Moreover, the chemistry of the as-synthesized carbon nitrides has been widely neglected. Here we report that some of these handicaps might be overcome by a controllable and reversible protonation. It was found that protonation not only provides better dispersion and exposes a high surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
514
2
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 753 publications
(547 citation statements)
references
References 23 publications
20
514
2
11
Order By: Relevance
“…The most efficient metal-free photocatalyst is the graphitic carbon nitride (g-C 3 N 4 ). [74][75][76][77][78] For instance, Wang et al [79] reported that the carbon nitride (C 3 N 4 ) polymer can be easily modified by standard organic protocols. The copolymerization with barbituric acid was studied and realized the continuous band structure modification.…”
Section: Band Structure Engineering Through Crystal Structure Modificmentioning
confidence: 99%
“…The most efficient metal-free photocatalyst is the graphitic carbon nitride (g-C 3 N 4 ). [74][75][76][77][78] For instance, Wang et al [79] reported that the carbon nitride (C 3 N 4 ) polymer can be easily modified by standard organic protocols. The copolymerization with barbituric acid was studied and realized the continuous band structure modification.…”
Section: Band Structure Engineering Through Crystal Structure Modificmentioning
confidence: 99%
“…However, the photocatalytic efficiency of bare g-C 3 N 4 was relatively low and far from satisfactory. Several strategies have thus been adopted to enhance the photocatalytic performance of g-C 3 N 4 , including designing an appropriate textural porosity [15,16], doping with metal oxides or nonmetal elements [17][18][19], and exfoliation of bulk phase to nanosheets [20][21][22][23]. Though a lot of efforts have been exerted to prepare structurally new g-C 3 N 4 compounds, it is still a big challenge to manufacture g-C 3 N 4 materials with enhanced visible-light photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The heptazine core is also known as cyameluric nucleus, a name coined by Pauling [4] referring to cyameluric acid H 3 C 6 N 7 O 3 [5]. Although much of the current interest concerning heptazines initially originated from the "harder than diamond" considerations based on calculations for certain modifications of C 3 N 4 [6,7] additional properties (catalysis being a prominent example [3a, 8,9]) have recently broadened the focus of carbon nitride chemistry. Typically, many heptazine-containing compounds are synthesized based on the thermal condensation of melamine (2,4,6-triamino-s-triazine, C 3 N 3 (NH 2 ) 3 ).…”
Section: Introductionmentioning
confidence: 99%